Usability Evaluation of Social Media Web Sites and Applications via Eye-Tracking Method - (:unkn) unknown (IGI Global, 2016)
This chapter describes usability studies of website-based and mobile application-based social media sites. In the study including 10 university students, the completion time of assigned tasks were measured along with click numbers and completion situations. These measures were analyzed. Data obtained from eye tracking movements was analyzed, and the results were evaluated. According to the results, the users can complete most of the tasks, but completion time varied. The participants had difficulties completing settings menu tasks except menus previously used in social media. When eye tracking results were examined, it was revealed that they mostly focused on the left side of websites and mobile applications. The participants stated that mobile applications were more useful than websites. According to eye-tracking data obtained in the study and the users' opinions, mobile social media applications weremore functional than their websites. © 2017, IGI Global.